2020
DOI: 10.1111/jgs.16380
|View full text |Cite
|
Sign up to set email alerts
|

Motoric Cognitive Risk Syndrome in Polypharmacy

Abstract: OBJECTIVES: Risk factors for motoric cognitive risk syndrome (MCR), a predementia syndrome characterized by slow gait and cognitive complaints, have been identified, but few are reversible. Polypharmacy is a potentially reversible risk factor for cognitive decline, but the relationship between MCR and polypharmacy has not been examined. Our aim was to compare the epidemiology of MCR and polypharmacy. DESIGN: Cross-sectional. SETTING: Community-based Health and Retirement Study cohort. PARTICIPANTS: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…Older people were considered to have SCD only when they felt they had more memory problems than most people. By contrast, participants were diagnosed with SCD when their self-perceived memory was either poor or worse than before in other researches [ 6 , 49 ]. An alternative explanation is that our study participants were relatively healthy community residents rather than outpatients or inpatients, which may underestimate the prevalence of MCR.…”
Section: Discussionmentioning
confidence: 84%
“…Older people were considered to have SCD only when they felt they had more memory problems than most people. By contrast, participants were diagnosed with SCD when their self-perceived memory was either poor or worse than before in other researches [ 6 , 49 ]. An alternative explanation is that our study participants were relatively healthy community residents rather than outpatients or inpatients, which may underestimate the prevalence of MCR.…”
Section: Discussionmentioning
confidence: 84%
“…Já em relação as diferenças na velocidade da marcha de idosos com e sem a SRCM, Ayers e Verghese 31 analisaram os parâmetros da marcha e detectaram que os idosos com a síndrome apresentaram menor comprimento da passada e menor tempo da fase de balanço quando comparados aos idosos sem a SRCM. Na comparação entre os grupos de idosos com e sem a SRCM, deste estudo, não houve diferenças significativas entre os grupos para as variáveis baixa escolaridade, presença de doenças crônicas, polifarmácia, excesso de peso e inatividade física, o que diverge dos achados de pesquisas anteriores que demonstraram diferenças significativas para a presença dessas variáveis entre os grupos 13,32 .…”
Section: Discussionunclassified
“…Polypharmacy, which involves the usage of five or more regularly scheduled medications, has also been considered as a modifiable risk factor for MCR. A study in a total of 1,119 adults (≥65 years) in a cross-sectional cohort of Community-based Health and Retirement Study showed that polypharmacy, that marked for the medical co-morbidities and complexities, related with decline in the gait velocity and cognitive loss as compared with the ones without polypharmacy (George and Verghese, 2020 ). Polypharmacy appended the chances of adverse drug events and interactions, intentional and non-intentional medical adherence, and reduced treatment effectiveness that increased MCR through the metabolic and structural alterations in the brain (George and Verghese, 2020 ).…”
Section: Pathologymentioning
confidence: 99%